Evaluation of IL-8 and MEF25-75 in patients with severe COPD who were treated with combined therapy of ICSs / LABAs plus tiotropium bromide - Elena Jovanovska Janeva; Zlatica Gosheva; Angelko Gjorchev; Suzana Arbutina; Marija Zdraveska; Deska Dimitrievska; Dejan Todevski; Dejan Trajkov (Europian Respiratory Society, 2013)
The aim of this study was to determine the effect of combined therapy of ICSs/LABAs plus tiotropiumbromide in patients with COPD, by analyzing of IL-8 and MEF25-75 at the beginning and after 6 months oftherapy. The study included 33 patients with severe COPD. In each of them were measured serum IL-8levels by the ELISA method and MEF25-75 which are indicated the small airways obstruction. They weretreated with combined therapy of ICSs/LABAs (500mcg) plus Tiotropium Bromide (18mcg) daily in durationof 6 months. The results were statistically elaborated according to the T-test for Dependent Samples. Theobtained results of IL-8 showed that the level of IL-8 before the start of therapy were much higher and thattreatment significantly reduces their value (t=3.13, p=0.003, p<0.05). The results of MEF 25-75 at the startof therapy were lower and after 6 months of treatment showed a slight improvement of lung function butstatistically insignificant (t= -0.83, p=0.41,p<0.05). The concentration of IL-8 is closely related with airwayobstruction in patients with COPD and may serve as a marker for evaluating the severity of airwayinflammation. ICSs/LABAs and tiotropium bromide have inhibitory effect on neutrophilic inflammationthrough the suppression of IL-8 production from epithelial cells and thus may contribute to lower cellularinflammation in COPD. Because it is a progressive disease and airflow limitation is not fully reversible, wecannot expect spectacular results like we show with the value of MEF25-75, but should strive to preventprogression and reduce airway remodeling with education, pharmacologic and non pharmacologic treatment
Keywords: lung function testing; immunology; COPD - management